Attachment quality assessed from children's family drawings links to child conduct problems and callous-unemotional behaviors. Issue 3 (4th May 2021) - Rehder, Peter D.; Mills-Koonce, W. Roger; Wagner, Nicholas J.; Zvara, Bharathi; Willoughby, Michael T.
ABSTRACT: Objective: Recently, there has been considerable research on the origins of childhood conduct problems (CP) and callous-unemotional (CU) behaviors. This study examined associations between children's attachment representations and CP and CU behaviors during middle childhood. Method: At 1 st grade, 1, 292 children (57% European American, 42.5% African American, 0.5% other race; 50.9% girls) completed a drawing of their family, which was coded by trained raters to assess attachment representations. Primary caregivers reported on children's CP and CU behaviors. Results: Children with disorganized representations showed more CP and CU behaviors than children with secure and resistant representations. They were also more likely than those with secure representations to show elevated CP without CU behaviors, CU behaviors only, and co-occurring CP and CU behaviors. Conclusion: These findings provide support for attachment disorganization as a correlate of CP and CU behaviors and suggest that attachment representations are likely important proximal influences on children's behavior.